2008
DOI: 10.1186/1472-6750-8-56
|View full text |Cite
|
Sign up to set email alerts
|

Successful elimination of non-neural cells and unachievable elimination of glial cells by means of commonly used cell culture manipulations during differentiation of GFAP and SOX2 positive neural progenitors (NHA) to neuronal cells

Abstract: Background: Although extensive research has been performed to control differentiation of neural stem cells -still, the response of those cells to diverse cell culture conditions often appears to be random and difficult to predict. To this end, we strived to obtain stabilized protocol of NHA cells differentiation -allowing for an increase in percentage yield of neuronal cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 27 publications
4
12
0
Order By: Relevance
“…Among cells showing GFAP and MAP2 co-expression, most (about 70%) presented only the remnants of GFAP, which constitutes additional evidence that the neuronal cells originated from the cells initially showing a multilineage phenotype. The existence of MAP2+, GFAP+, CD44- cells has already been presented by our group [7]. We showed that the percentage of those cells after 5–7 days of neural differentiation did not exceed 5% [7].…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…Among cells showing GFAP and MAP2 co-expression, most (about 70%) presented only the remnants of GFAP, which constitutes additional evidence that the neuronal cells originated from the cells initially showing a multilineage phenotype. The existence of MAP2+, GFAP+, CD44- cells has already been presented by our group [7]. We showed that the percentage of those cells after 5–7 days of neural differentiation did not exceed 5% [7].…”
Section: Resultssupporting
confidence: 55%
“…The existence of MAP2+, GFAP+, CD44- cells has already been presented by our group [7]. We showed that the percentage of those cells after 5–7 days of neural differentiation did not exceed 5% [7]. …”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…2A and B). The NPs also expressed GFAP, an astrocyte and neural progenitor cell marker (Schwartz et al, 2003;Witusik et al, 2008). In addition, immunoreactivity was detected for Oct-4, a marker for hESC pluripotency, although the gel electrophoresis product band was weak.…”
Section: Genementioning
confidence: 96%
“…This consequently could have resulted in a value more than 100% for the combined percentages of cells that stained positive for the examined markers in GS‐2 and D3 cell lines. In this context, previous studies, based on the culture of brain‐derived cells, have also shown coexpression of these neural markers in neural progenitors (Witusik et al, 2008), astrocytes (Dráberová et al, 2008), and brain parenchymal cells (Rieske et al, 2007).…”
Section: Discussionmentioning
confidence: 81%